Comparison of pre-treatment with different diluted sufentanil in reducing propofol injection pain in gastrointestinal endoscopy: A randomized controlled study. - Qian Su; Shu He; Lu Li; Xiangqing Wei; Xin Sun; Xuefeng Yang; Boxiang Du; Lei Yao (PLoS ONE)
Background This study aimed to investigate the efficacy of pre-treatment with different concentrations of sufentanil in mitigating propofol injection-induced pain. Methods This study included 421 patients who were scheduled for gastrointestinal endoscopy between June 2023 and December 2024. Participants were randomly assigned to one of the four groups with different concentrations sufentanil: 0 µg/mL group(0.9% normal saline), 0.5 µg/mL group, 1 µg/mL group and 5 µg/mL group. Results Among the four groups, the rates of pain relief were 82 (77.4%), 93 (89.4%), 96 (89.7%), and 91 (87.5%), respectively. Compared to the 0 µg/mL group, the other groups demonstrated significantly reduced pain following propofol injection (p < 0.05). The recovery times were 14.59 ± 3.92 min, 15.13 ± 3.20 min, 14.27 ± 3.06 min, and 15.57 ± 3.24 min, respectively. Notably, the 1 µg/mL group did not exhibit a prolonged recovery time compared to the 0 µg/mL group. The total propofol consumption was recorded as 218.5 ± 36.8 mg, 196.7 ± 31.0 mg, 183.8 ± 25.0 mg, and 189.6 ± 31.4 mg, respectively, with the 1 µg/mL group showing the lowest total propofol consumption among the groups. The incidences of adverse events (AEs) were 61.3%, 70.2%, 58.9%, and 76.9%, respectively. In comparison to the 1 µg/mL group, the 5 µg/mL group exhibited a higher incidence of AEs. Furthermore, multivariate analysis indicated that a 5 µg/mL dilution of sufentanil increases the risk of AEs (p < 0.05). Conclusions The 1 µg/mL group demonstrated greater safety and efficacy when combined with propofol. Trial registration The study has been registered in the Chinese Clinical Trial Registry (ChiCTR). Link of the registry: http://www.chictr.org.cn. Date of registration: 2023/06/12. Trial registration number: ChiCTR2300072402.